An Interdisciplinary Approach to Documenting Knowledge: Plants and Their Uses in Southern Greenland - Whitecloud, Simone S.; Grenoble, Lenore A. (ARCTIC, 2014)
The native language of west Greenland, Kalaallisut, is robust, with over 50 000 speakers among approximately 56 000 inhabitants. However, many people in Nuuk, the capital and largest city, believe traditional knowledge of plant uses has been lost as a result of extensive Danish contact. Our findings indicate that in southern Greenland local knowledge of plant uses is greater than believed. Interviews conducted with people in two southern communities, Nanortalik and Qassiarsuk, showed that people acquire knowledge about plants through a vast number of resources, not only Inuit knowledge from elders, but also published European sources and experimentation, raising questions about the extent to which such knowledge can be labeled traditional or ancestral. We documented more than 50 taxa and 205 plant uses in seven broad categories: medicine, beverages, food, herbs and spices, fuel, ritual, and material culture, the last category consisting primarily of decorative uses. Although medicinal uses account for the largest amount (~27%), the combination of the food, beverage, and herbs and spices/condiment categories make up nearly half of all uses. Some plants, in particular mushrooms and seaweed, were identified as edible but are not consumed. All consultants are fluent speakers of Kalaallisut, and identified the majority of plants. However, only 12 species were identified by everyone consulted, and some plants were identified by their Danish name. Some plant names and uses have remained consistent along the migration route of Inuit ancestors across the Arctic, while others have been lost or changed over time. La langue autochtone de l’ouest du Groenland, le kalaallisut, est une langue robuste. Elle est parlée par plus de 50 000 personnes relevant d’une population d’environ 56 000 habitants. Cependant, de nombreuses personnes de Nuuk, la capitale et également la plus grande ville du pays, croient que les connaissances traditionnelles des plantes se sont perdues en raison des contacts trop grands avec les Danois. Nos ...